Demon of the Lost Cause : Sherman and Civil War history - Moody, Wesley (Shades of blue and gray series., 2011)
At the end of the Civil War, Union general William Tecumseh Sherman was surprisingly more popular in the newly defeated South than he was in the North. Yet only thirty years later, his name was synonymous with evil and destruction in the South. Here, historian Wesley Moody examines these perplexing contradictions and how they and others function in past and present myths about Sherman. Demon of the Lost Cause reveals the machinations behind the Sherman myth and the reasons behind the acceptance of such myths, no matter who invented them. In the case of Sherman's own mythmaking, Moody postulates that his motivation was to secure a military position to support his wife and children. For the other Sherman mythmakers, personal or political gain was typically the rationale. In tracing Sherman's ever-changing reputation, Moody sheds light on current and past understanding of the Civil War through the lens of one of its most controversial figures.--From publisher description.